Clinical Trial Progress and Application of Immune Checkpoint Inhibitors in the Treatment of Small Cell Lung Cancer - Huiqiu ZHANG (Chinese Anti-Cancer Association; Chinese Antituberculosis Association, 2021)
Small cell lung cancer (SCLC) is a neuroendocrine tumor with fast progression, high malignancy, easy recurrence, and extremely poor prognosis. In the past 30 years, the clinical treatment strategy of SCLC has been mainly chemotherapy and radiotherapy, but the curative effect is not significant; the current immunotherapy of SCLC has gradually entered the clinic and has made certain progress. Tumor immunotherapy includes immune checkpoint inhibitors, tumor vaccines, cytokines, chimeric antigen receptor T-cell immunotherapy (CAR-T) therapy, etc. Currently, immune checkpoint inhibitors are the most widely used. This article summarizes the principles of immune checkpoint inhibitors and related drugs, summarizes their domestic and foreign clinical trials progress in SCLC treatment, reviews the biomarkers used in the therapy, and discusses its future development direction.